The Role of Autologous Stem Cell Transplantation in the Treatment of Diffuse Large B-Cell Lymphoma - Marco Gunnellini; Rita Emili; Stefano Coaccioli; Anna Marina Liberati (Advances in Hematology)
Diffuse large B-cell non-Hodgkin’s lymphoma (DLBCL) accounting for approximately 30% of new lymphoma diagnoses in adult patients. Complete remissions (CRs) can be achieved in 45% to 55% of patients and cure in approximately 30–35% with anthracycline-containing combination chemotherapy. The ageadjusted IPI (aaIPI) has been widely employed, particularly to “tailor” more intensive therapy such as high-dose therapy (HDT) with autologous hemopoietic stem cell rescue (ASCT). IPI, however, has failed to reliably predict response to specific therapies. A subgroup of young patients with poor prognosis exists. To clarify the role of HDT/ASCT combined with rituximab in the front line therapy a longer follow-up and randomized studies are needed. The benefit of HDT/ASCT for refractory or relapsed DLBCL is restricted to patients with immunochemosensitive disease. Currently, clinical and biological research is focused to improve the curability of this setting of patients, mainly young.